Economic Dimension and Empowerment among Rural and Urban Women in Nepal: Analysis from 2016 Nepal Demographic and Health Survey - Karki, Rita Devi; Thapa, Naba Raj (Humanities and Social Sciences Journal, 2022)
Economic background is taken as one of the crucial influencing factors of women's empowerment. This paper attempts to assess the key economic features of women and their degree of association on empowerment by place of residence. For this, the Nepal Demographic and Health Survey, 2016 data were used. In total, 9,875 currently married women aged 15-49 years were used to analyze by applying descriptive and bivariate analysis techniques. The findings showed rural women have poor economic status compared with urban women. Agriculture is the main profession of women among both rural and urban areas but the non-agricultural profession is lower especially among rural (11.7%) women to compare with urban (24.6%) women. Similarly, unpaid work seems still prevalent in both urban (46.6%) and rural (59.6%) areas. The male domination is clearly observed in earning a position with their husband, being paid in the same job, and ownership of property related to land and house. The study showed that there is a positive and significant relationship between working women and their empowerment in both rural and urban areas. The better economic status of women has higher empowerment in comparison to the women who have poor status. Hence, economic power has an automatically positive influence on women's empowerment. However, it needs to be paid high attention to improve the prevailing poor women’s economic status in different circumstances.